Where the Souls Rest - Papazov, Boyan (Bulgaria, 1998)
Soros Documentary Fund In the last two centuries historic sources refer to the Karakachans as semi nomads who along with their families and the entire households have been traveling from the alpine mountains to the warm lowlands of the Balkan Peninsula in search of pastures for their flocks. This episode from the TV series “Where Souls Rest” records the oral history and the culture of the Karakachans as manifested in religious rites and feasts. A film about a rather invisible minority: the Karakachans.